1999
DOI: 10.1007/s004150050453
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of isolated optic neuritis: the risk of developing multiple sclerosis, its outcome, and the prognostic role of paraclinical tests

Abstract: We evaluated the risk of developing clinically definite multiple sclerosis (CDMS) after an acute attack of isolated optic neuritis (ON) in 112 patients, in relation to demographic and paraclinical findings. Patients were examined by brain MRI, CSF analysis, and multiple evoked potentials (EPs); 10 were lost to follow-up, and the other 102 were enrolled in a prospective study (follow-up duration 6. 3 +/- 2.2 years). Of these, 37 (36.3%) developed CDMS after a mean interval of 2.3 +/- 1.6 years. The risk of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 44 publications
6
70
0
1
Order By: Relevance
“…First, the largest subgroup had op- tic neuritis, which may have a milder disease course; 70 to 80 percent have minimal disability after followup periods of 8 to 15 years. 1,28 Second, all patients were followed prospectively whether multiple sclerosis developed or not, with assessment at regular intervals (1, 5, 10, and 14 years after onset); this helped detect cases of multiple sclerosis in patients in whom relapses were mild and disability was minimal. Third, patients with primary progressive multiple sclerosis were not included in the present study but have been in other studies 27,29 ; disability develops more rapidly in this subgroup than in those with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…First, the largest subgroup had op- tic neuritis, which may have a milder disease course; 70 to 80 percent have minimal disability after followup periods of 8 to 15 years. 1,28 Second, all patients were followed prospectively whether multiple sclerosis developed or not, with assessment at regular intervals (1, 5, 10, and 14 years after onset); this helped detect cases of multiple sclerosis in patients in whom relapses were mild and disability was minimal. Third, patients with primary progressive multiple sclerosis were not included in the present study but have been in other studies 27,29 ; disability develops more rapidly in this subgroup than in those with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…There were 22 such studies identified. 14,15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] All of these articles considered the risk of developing CDMS in patients with CIS, based on the presence or absence of MRI lesions within the brain or spinal cord. The studies differed with respect to the number of patients included, the length of follow-up, and the definition of an abnormal scan (table E-5, available online at www.neurology.org).…”
Section: Methodsmentioning
confidence: 99%
“…34 After 10 years, the cumulative probability of developing CDMS in patients with abnormal MRI (one or more white matter lesions consistent with MS) was approximately 55% after 10 years compared to 0% in patients without such lesions. No alternative diagnosis to MS or optic neuritis is mentioned in this report.…”
Section: Analysis Of the Evidence Relationship Of Nonenhancing Baselmentioning
confidence: 97%
“…17 In 20% of patients, optic neuritis is the first manifestation of multiple sclerosis, 18 and in 38% multiple sclerosis develops within 10 years. [19][20][21] Although optic neuritis is used to study demyelination, the mechanisms of damage and repair in this disease are not completely understood. Moreover, there are no effective treatments to improve vision for people who have this condition.…”
Section: Introductionmentioning
confidence: 99%